2021
DOI: 10.1021/acsestwater.1c00176
|View full text |Cite
|
Sign up to set email alerts
|

Human–Infrastructure Interactions during the COVID-19 Pandemic: Understanding Water and Electricity Demand Profiles at the Building Level

Abstract: When engineers design and manage a building’s water and electricity utilities, they must make assumptions about resource use. These assumptions are often challenged when unexpected changes in demand occur, such as the spatial and temporal changes observed during the coronavirus (COVID-19) pandemic. Social distancing policies (SDPs) enacted led many universities to close their campuses and implement remote learning, impacting utility consumption patterns. Yet, little is known about how consumption changed at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Social distancing policies enacted in March 2020 during the initial wave of the coronavirus (COVID-19) pandemic to limit disease spread , caused widespread building closures in the nonresidential sector (i.e., commercial, industrial, etc.). This limited building occupancy and altered individual and societal behaviors (e.g., hygiene practices), which significantly impacted water demand. The impact of policy interventions related to the COVID-19 pandemic on water demand has recently been addressed. Several studies have reported significant reductions in water demand across buildings in nonresidential sectors. , For example, Li et al reported a decrease of 11.6% in water demand across buildings in California (United States), while Kalbusch et al documented reductions in water demand, ranging between 30% and 53%, across buildings in Joinville, Brazil. In contrast, reports on residential sectors indicate increases in water demand, as well as anomalies in the timing and magnitude of water demand peaks. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social distancing policies enacted in March 2020 during the initial wave of the coronavirus (COVID-19) pandemic to limit disease spread , caused widespread building closures in the nonresidential sector (i.e., commercial, industrial, etc.). This limited building occupancy and altered individual and societal behaviors (e.g., hygiene practices), which significantly impacted water demand. The impact of policy interventions related to the COVID-19 pandemic on water demand has recently been addressed. Several studies have reported significant reductions in water demand across buildings in nonresidential sectors. , For example, Li et al reported a decrease of 11.6% in water demand across buildings in California (United States), while Kalbusch et al documented reductions in water demand, ranging between 30% and 53%, across buildings in Joinville, Brazil. In contrast, reports on residential sectors indicate increases in water demand, as well as anomalies in the timing and magnitude of water demand peaks. , …”
Section: Introductionmentioning
confidence: 99%
“… 4 10 Several studies have reported significant reductions in water demand across buildings in nonresidential sectors. 5 , 8 10 For example, Li et al reported a decrease of 11.6% in water demand across buildings in California (United States), while Kalbusch et al documented reductions in water demand, ranging between 30% and 53%, across buildings in Joinville, Brazil. In contrast, reports on residential sectors indicate increases in water demand, 6 9 as well as anomalies in the timing and magnitude of water demand peaks.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] While short periods of reduced water use (e.g., nights, weekends, school breaks) are common in building plumbing, many buildings were closed or at reduced occupancy for several months during the COVID-19 pandemic. [6][7][8][9][10] Reduced water use is associated with decreased disinfectant residual levels, equilibration of hot and cold water temperatures with building temperature, and potential for increased concentrations of contaminants such as disinfection byproducts, metals, and opportunistic pathogens. [11][12][13][14][15][16][17][18][19][20][21] Legionella pneumophila, the causative agent of Legionnaires' disease and Pontiac fever, was of particular concern because its occurrence is widely assumed to be associated with low water use, [22][23][24][25][26] and disease incidence is rising around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal hot water setpoint of 45°C with 2 days operated at 60°C; 5 green building;6 Approximate number of 229 fixtures includes only the following potable fixtures: faucets in bathrooms and kitchens, drinking water fountains and 230 bottle filling stations, and showers.…”
mentioning
confidence: 99%
“…The study focuses on how the research sub-sector adapted rapidly during the pandemic and continued providing water and sanitation services, contributing to reducing the spread of the virus. To our knowledge, this is the first work to undertake such a study as previous studies tended to focus on the relationships between infrastructure with water and electricity and working environment [16] and the implications of social distancing policies on drinking water infrastructure [17]. Other studies focused on the opportunities and challenges of water and wastewater utilities during the pandemic [18][19][20].…”
Section: Introductionmentioning
confidence: 99%